(untitled) - Frieden, B. Roy (Cambridge, U.K., 2004)
This work presents a scientific theory of measurement that is largely a quantification of the ideas that "All things physical are information-theoretic in origin and this is a participatory universe" and "Observer participancy gives rise to information; and information gives rise to physics" (as stated by physicist J.A. Wheeler). Frieden (emeritus, optical sciences, U. of Arizona) believes that the derivation of scientific laws can be unified under the theory of measurement, in which Fisher information is seen to flow from a physical source effect to a data space. His "extreme physical information" (or EPI) approach uses knowledge of the information flow in the measurement process to derive the mathematical forms of physics, including relativistic quantum mechanics, general relativity, and classical statistical physics.
Keywords: Physical measurements,Information theory,Physics; Methodology